Tradisi Ngandang Jum’atan di Daerah Waringinkurung: Study Living Hadis - Nurmawan Nurmawan; Ola Alifiyanti Zahra Purnama (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research reviews the Friday ngandang tradition in the Waringinkurung area. This research aims to discuss friendship and kinship found in this tradition. This research uses qualitative methods and the research instruments are observation and interviews. The data sources for this research are the results of interviews from several Waringinkurung residents and previous research journals. The result is that in Waringinkurung, the Ngandang Friday tradition is a way to apply Islamic values about friendship and kinship. After Friday prayers, this ritual is carried out by sharing prayers, shaking hands and eating together. This tradition has spiritual meaning and helps strengthen family relationships that are often broken due to daily activities